Adaptasi Pola Permainan Dangdut Gaya New Pallapa Pada Komunitas Pemusik Dangdut di Kec, Selo, Kab. Boyolali - Suranto, Suranto (GETER : Jurnal Seni Drama, Tari dan Musik, 2024)
This study explores the adoption of the Pallapanan style of dangdut music by musicians and music communities in Selo, Boyolali District, Central Java. Originating from the "New Pallapa" music group in East Java, the Pallapanan style is characterized by unique playing patterns, particularly in rhythm keyboards, ketipung drums, and bass instruments, which distinguish it from other dangdut music styles. This research investigates the distribution of the Pallapanan style, forms of its adoption, and the impacts on the adaptive behavior of Selo’s musicians and dangdut music community. The study employs a qualitative approach, drawing on Ghufron and Rini's psychological adaptation theory, which frames adaptation as self-regulated behavior in response to environmental challenges or threats to well-being. Data were collected through interviews, field observations, and analysis of online media content showcasing "New Pallapa" performances. Findings reveal that internet media, particularly recorded videos of "New Pallapa" performances, is the primary driver of the Pallapanan style's spread in Selo. The adoption process involves imitating playing patterns, instrumental techniques, and vocal styles. This adaptation has led to skill development among musicians, the creation of job opportunities, and shifts in audience behavior, highlighting the transformative impact of this stylistic adoption on the local dangdut scene. This study contributes to the understanding of musical adaptation and cultural diffusion in the context of regional music trends, providing insights into the interplay between digital media, community practices, and artistic evolution in traditional music genres.